TEACHING ENGLISH GENERIC NOUNS: THE EXPLORATION OF THE GENERIC IDEA IN ENGLISH AND INDONESIAN AND THE APPLICATIONS OF EXPLICIT INSTRUCTION IN CLASSROOM - David Wijaya (Indonesian JELT, 2012)
Although the generic idea is often expressed in discourse, the acquisition of it is so slow among learners. Moreover, this idea is expressed through a highly complex system of the English language called the article system. As a result, learners tend to make errors when they attempt to convey the generic idea in their output. Since the Indonesian language has a different way to express the generic idea, Indonesian learners of English may be interfered by their first language when expressing this idea. Consequently, errors are inevitable. A thorough examination at how the generic idea is expressed in English and in Indonesian is perhaps the only way to understand this complexity. To help learners express the idea correctly and appropriately, teachers should give explicit instruction in forms of mini lesson and explicit corrective feedback (i.e. metalinguistic feedback). This article presents all the patterns to express the generic idea both in English and Indonesian, poses some pedagogical implications and discusses some useful approaches for English teachers in dealing with it.